ANALISIS PENGARUH KETIDAKHADIRAN PEKERJAAN AYAH TERHADAP KEHARMONISAN KELUARGA, MENTAL IBU DAN PERKEMBANGAN ANAK: TERKAIT PERAN EKONOMI DALAM KELUARGA - Anna Mukliha; Fauzana Annova (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the effects on mothers and children in terms of mental and self-development and family harmony related to the absence of a father's job. Many factors influence the role of the father missing in shaping mental and emotional health in children, one of which will be discussed in this article is the absence of a father's job in the family. In writing this article, the author uses a type of field research or empirical research, where researchers collect data directly from the source. This study collects information and data in depth through individuals or groups and the results of previous studies that are appropriate and other references in order to obtain answers and theoretical basis regarding the problems studied. The data collection technique applied in this study is to collect data from scientific works in the form of books, journals, magazines, theses, theses, and various other scientific papers both online and offline. This study is slightly different from the fatherless case, because the discussion of Fatherless is more about the condition where the absence of a father figure in accompanying and educating children during their growth. This can be caused by divorce, death, and many other things. However, in the case that I studied, it discusses the mentality of the mother and child more deeply because the absence of a father's job causes the father's role to be replaced by the mother, starting from educating children to earning a living. The results of this study are the lack of harmony in the family, especially between the mother and father, especially between the father and child. The absence of a father's job in family life causes children to have low self-esteem when they are adults, tend to have feelings of shame, anger because they feel different, children do not get a living from their father like other children. Children who are raised without a living from a father have a low mentality for life, and even tend to dislike their father.